We have a sequence where we know that the initial term a0 is 25.
![a_0=25](https://img.qammunity.org/2023/formulas/mathematics/college/zp8obveloga0altanldh7vha7esdhm3s64.png)
Then, each term adds the common difference of 15, so we can write:
![a_n=a_(n-1)+15](https://img.qammunity.org/2023/formulas/mathematics/college/7zqemb3943ilk2actb8wdo1o9pz8ojonyb.png)
The recursive formula for this sequence, representing how much she has in her savings account, is a(n) = a(n-1) + 15.
To find the explicit formula, we relate each term to the first term in order to find the relation:
![\begin{gathered} a_1=a_0+15=25+15 \\ a_2=a_1+15=(25+15)+15=25+2\cdot15 \\ a_n=25+n\cdot15=25+15n_{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wq3zbb5d2g91q9mnfx4i5j43iaxfipbwar.png)
Then, the explicit formula is a(n) = 25 + 15n.
Answer:
Recursive formula: a(n) = a(n-1) + 15
Explicit formula: a(n) = 25 + 15n